2001
DOI: 10.1006/brcg.2001.1286
|View full text |Cite
|
Sign up to set email alerts
|

Preserved Implicit Learning on Both the Serial Reaction Time Task and Artificial Grammar in Patients with Parkinson's Disease

Abstract: Thirteen non-demented patients with Parkinson's disease (PD) were compared with age matched controls on two standard tests of implicit learning. A verbal version of the Serial Reaction Time (SRT) task was used to assess sequence learning and an artificial grammar (AG) task assessed perceptual learning. It was predicted that PD patients would show implicit learning on the AG task but not the SRT task, as motor sequence learning is thought to be reliant upon the basal ganglia which is damaged in PD. Patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
66
2
4

Year Published

2002
2002
2010
2010

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(75 citation statements)
references
References 41 publications
3
66
2
4
Order By: Relevance
“…In an effort to address the role of inherent motor expression difficulties, PD subjects have been tested by using a verbal version of the SRT task. As in many other studies, the results have not been consistent, with one group of subjects showing learning (Smith et al, 2001), while in another group there was no effect (Westwater et al, 1998). Such mixed results across studies, combined with the finding that the clinical stage of the disease does not seem to influence the rate or the magnitude of implicit learning in PD (Stefanova et al, 2000), imply that the extent of motor symptoms is not related to the amount of implicit learning that occurs.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…In an effort to address the role of inherent motor expression difficulties, PD subjects have been tested by using a verbal version of the SRT task. As in many other studies, the results have not been consistent, with one group of subjects showing learning (Smith et al, 2001), while in another group there was no effect (Westwater et al, 1998). Such mixed results across studies, combined with the finding that the clinical stage of the disease does not seem to influence the rate or the magnitude of implicit learning in PD (Stefanova et al, 2000), imply that the extent of motor symptoms is not related to the amount of implicit learning that occurs.…”
Section: Discussioncontrasting
confidence: 56%
“…However, inconsistency of impairments observed in patients with Parkinson's disease (PD), who have significant dysfunction of the basal ganglia, have raised the issue of whether these structures play a crucial role in implicit sequence learning or merely modulate the expression of the learning. Although some studies have found these patients to have profound implicit learning deficits (Pascual-Leone et al, 1993;Jackson et al, 1995;Doyon et al, 1997;Stefanova et al, 2000), others observed either no (Smith et al, 2001) or only mild to moderate impairments (Pascual-Leone et al, 1993;Sommer et al, 1999;Ferraro et al, 1993;Shin and Ivry, 2003).…”
Section: Introductionmentioning
confidence: 92%
“…Subjects in later stages of PD, with bilateral involvement, or subjects with additional frontal type deficits were the most affected (Jackson et al 1995;Doyon et al 1997). However, there are also reports of preserved implicit learning of PD subjects in the SRTT (Smith et al 2001). Even in those investigations that demonstrated less implicit learning in PD or HD subjects than in normal controls, basal ganglia subjects still showed a substantial decrease in reaction times in response to a repeating sequence and a slowing of responses when a random block was introduced.…”
mentioning
confidence: 98%
“…After some amount of practice, performance of participants on the repeated sequence is generally better than performance on a new sequence. In recent years, a huge number of studies using SRT tasks have improved our knowledge about various issues, such as the implicit-learning abilities of children (e.g., Meulemans, Van Der Linden, & Perruchet, 1998), elderly people (e.g., Curran, 1997), and neurologically impaired patients (e.g., Smith, Siegert, McDowall, & Abernethy, 2001), the relationships between performance and explicit knowledge (e.g., Shanks & Perruchet, 2002), and the relationships between perceptual and motor components of learning (e.g., Kelly, Burton, Riedel, & Lynch, 2003).…”
mentioning
confidence: 99%